Understanding copyright : intellectual property in the digital age - Klein, Bethany; Moss, Giles; Edwards, Lee (Lee M. S.) (2015)
How cultural property is created, governed, protected, circulated and accessed raises serious questions for individuals, activists and governments. Taking a rounded view of the debates and perspectives that have emerged as essential to the struggle over copyright in the digital age, this book: * Looks across a broad range of industries including music, television and film to consider the issues of media power and policy. * Is packed with gripping examples and case studies, including pirate bay, Google books, Metallica v Napster, Aaron Swartz/JSTOR and megaupload.com * Features boxed case studies and guided further reading lists. Edited with authority and insight, this book offers students and scholars of cultural and media industries, new media and social media a comprehensive overview of the contemporary issues surrounding intellectual property.
Keywords: Copyright infringement; Copyright; Copyright; Copyright infringement